Freshwater-seawater transition in coastal Todos Santos aquifer, Baja California Sur. (October 2018) - Mahlknecht, Jürgen; Sanford, William E.; Fichera, Marissa; Mora, Abrahan
Abstract: Todos Santos is a coastal town located in Baja California Sur (Mexico), which has experienced an increase in tourist and agricultural activities during the last years. However, the Todos Santos aquifer is the sole source of freshwater supplied to populations. Therefore, the goal of this work is to investigate the processes that can cause groundwater salinity in this aquifer. The results of the chemical analysis performed in groundwater indicate 3 water groups: i) less mineralized waters of the recharge zones showing a strong interaction with silicate rocks; ii) transition-zone waters from alluvial sediments also reflecting silicate rock-water interaction; iii) the most mineralized waters located along the coastline reflecting seawater intrusion. Overall, the ionic composition and the salinity gradient of groundwater are in agreement with the topographic flow paths. Nevertheless, in wells located in the coastline, groundwater interacts with seawater and undergoes evaporation simultaneously, exponentially increasing the salinity beyond seawater composition.